Decision Support System For Determining The Best Lecturers And Students In The Information Technology Study Program, UM Palembang Using The Multi Attribute Utility Theory Method - Apriansyah, Apriansyah; Muhammad Alfatur Rakhman (SEAN Institute, 2024)
Evaluation of lecturer performance and student achievement is an important step to maintain academic quality in higher education. The Information Technology Study Program at Universitas Muhammadiyah Palembang requires an efficient and objective system to select the best lecturers and students, considering their role in improving academic quality and institutional reputation. This study aims to develop a technology-based decision support system (DSS) to improve the automation and accuracy of the selection process. Using the Multi Attribute Utility Theory (MAUT) method, various assessment criteria are processed into standardized scores, allowing for objective assessment of lecturers and students. The Rapid Application Development (RAD) method is used in system development to ensure the process is fast and effective. This system is designed using various modeling diagrams, such as flowcharts, use case diagrams, and class diagrams, to ensure a clear, structured, and easily understood workflow for users, including administration and academics.The test results show that this system facilitates the selection process, reduces processing time, and minimizes errors that often occur in manual assessments. In addition, this system increases the transparency of assessments, provides objective, accurate, and accountable results, and encourages healthy competition among lecturers and students. The success of this implementation is expected to become a standard for periodic assessment in higher education. In addition, this system has the potential to be developed into a web-based application, which allows wider access for the entire academic community and increases the accessibility and effectiveness of the selection process in the future.